Economists in the PITS? - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2009)
Academic economists today are caught in a Publication Impossibility Theorem System or PITS. To further their careers, they are required to publish in A-journals, but this is impossible for the vast majority because there are few slots open in such journals. Such academic competition is held to provide the right incentives for hard work, but there may be serious negative consequences: the wrong output may be produced in an inefficient way, the wrong people may be selected, and the losers may react in a harmful way. The paper suggests several ways for improvement.
Keywords: A1; D02; I23; 330; Academia; economists; publication; journals; incentives; economic methodology; Wirtschaftswissenschaftler; Publikationsanalyse; Wettbewerb; Ökonomischer Anreiz; Extensives Spiel; Kritik